2004
DOI: 10.1021/es049830t
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Decomposition of 15 Polybrominated Diphenyl Ether Congeners in Methanol/Water

Abstract: Among all brominated flame retardants in use, the polybrominated diphenyl ethers (PBDEs) have been identified as being of particular environmental concern due to their global distribution and bioaccumulating properties, as observed in humans and wildlife worldwide. Still there is a need for more data on the basic characteristics of PBDEs to better understand and describe their environmental fate. Hence, the aim of this study was to investigate the photochemical degradation of PBDEs with different degrees of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
296
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 357 publications
(336 citation statements)
references
References 20 publications
28
296
6
Order By: Relevance
“…Similar results have been reported previously (Harrad and Hunter, 2006;Hu et al, 2011). Longer half-life and higher volatility of BDE-47 compared to BDE-99 can be an important reason that BDE-99 to BDE-47 ratio in atmosphere was lower than those in commercial products (Eriksson et al, 2004). Relatively high ratios of BDE-17 (0.06), BDE-28 (0.56), and BDE-66 (0.31) to BDE-47 were also found in this study compared to the ratios of DE-71 (0.0018, 0.0065, 0.014) and Bromkal 70-5DE (0.0012, 0.0023, 0.0049) (La Guardia et al, 2006), because higher brominated PBDEs are less volatile (Watanabe and Sakai, 2003).…”
Section: Pbde Congener Profilessupporting
confidence: 90%
“…Similar results have been reported previously (Harrad and Hunter, 2006;Hu et al, 2011). Longer half-life and higher volatility of BDE-47 compared to BDE-99 can be an important reason that BDE-99 to BDE-47 ratio in atmosphere was lower than those in commercial products (Eriksson et al, 2004). Relatively high ratios of BDE-17 (0.06), BDE-28 (0.56), and BDE-66 (0.31) to BDE-47 were also found in this study compared to the ratios of DE-71 (0.0018, 0.0065, 0.014) and Bromkal 70-5DE (0.0012, 0.0023, 0.0049) (La Guardia et al, 2006), because higher brominated PBDEs are less volatile (Watanabe and Sakai, 2003).…”
Section: Pbde Congener Profilessupporting
confidence: 90%
“…27 The photodegradation half-lives for the pentaBDE components decrease as follows: BDE100 > BDE47 > BDE99 indicating that BDE99 is the most photolabile of these three BDE congeners. 28,29 Therefore, the low level of BDE99/100 associated with the aerosol particles likely indicates that BDE99 is photodegraded during LRAT from source regions during the austral spring and summer when the air samples were collected. In Alert, Canada, the average ratio of BDE 99/100 was 5.4(±1.4) and 47/99 1.1(±0.26) (giving a ratio of 47/100 of ~5.9).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have demonstrated that BDE congeners can debrominate as a result of exposure to UV rays (Eriksson et al 2004;Söderström et al 2004). However, the decomposition products were not identified in these papers.…”
Section: Environmental Management and Sustainable Developmentmentioning
confidence: 99%